2019
DOI: 10.1039/c8fo01738g
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the anti-proliferation mechanism and bioactive compounds in red kidney bean coat against B16-F10 melanoma cells by metabolomics and network pharmacology analysis

Abstract: In this study, coat (RKBC) and kernel (RKBK) extracts of red kidney bean were prepared, and their chemical compositions and potential anti-cancer activity against B16-F10 cells were evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…A database search revealed a total of 256 previously reported compounds related to the B16F10 cell line [ [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] ]. In four of these studies, LC-MS was used for instrumental analysis [ [22] , [23] , [24] , [25] ] while NMR was employed in nine cases [ [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] ]. In vivo metabolomics was considered in eight cases [ 22 , [29] , [30] , [31] , [32] , [33] , [34] , [35] ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A database search revealed a total of 256 previously reported compounds related to the B16F10 cell line [ [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] ]. In four of these studies, LC-MS was used for instrumental analysis [ [22] , [23] , [24] , [25] ] while NMR was employed in nine cases [ [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] ]. In vivo metabolomics was considered in eight cases [ 22 , [29] , [30] , [31] , [32] , [33] , [34] , [35] ].…”
Section: Resultsmentioning
confidence: 99%
“…In the current investigation, 42 biologically relevant compounds were putatively determined ( Table 1 ). Among them, 21 metabolites were found in the literature as described above ( Table S1 ) [ [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] ]. The different numbers of detected and identified compounds as compared to the literature might be due to the different sample preparation techniques and/or different instrumental platforms used in the particular experiments, and/or different matrices employed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Several studies have discovered and demonstrated the potential mechanism of drug treatment of CM or inhibition of CM metastasis through network pharmacology, which also provides a new idea for this study. [16][17][18] Therefore, this study aims to combine network pharmacology and basic experiments to initially explore the potential mechanism of PN intervention in CM metastasis through network pharmacology and to demonstrate our network pharmacology results through cellular experiments. Providing theoretical and experimental support for clinical application of traditional Chinese medicine and drug research and development.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the rise of network pharmacology, has provided a scientific and inexpensive method for exploring the underlying mechanism of drug action on disease 15 . Several studies have discovered and demonstrated the potential mechanism of drug treatment of CM or inhibition of CM metastasis through network pharmacology, which also provides a new idea for this study 16–18 …”
Section: Introductionmentioning
confidence: 99%